Effects of organic manures and chemical fertilizers on the yield of brinjal and soil properties (Journal of the Bangladesh Agricultural University, 2010)
A field experiment was conducted at the Horticultural Farm of Bangladesh Agricultural University (BAU), Mymensingh during the period from December 2004 to April 2005 to evaluate the effect of manures and fertilizers on the yield of brinjal. There were five treatments consisting of organic, inorganic and combined sources of nutrients, of which the combined treatment (60 % organic +40% inorganic) showed the best performances. The maximum branching (20.1) with the highest number fruits/plant (15.2), fruit length (14.1 cm) and fruit diameter (4.3 cm) were found combined application of manures and fertilizers. The highest yield (45.5 t ha-1) was also obtained from the combined application of organic and inorganic sources of nutrients. Application of mustard oil cake or poultry manure alone gave better performance compared to only chemical fertilizers. The organic matter content and availability of N, P, K and S in soil were increased by organic matter application. On the other hand soil pH was increased with chemical application than organic. Keywords: Manure; Fertilizer; Yield; Brinjal; Soil properties DOI: 10.3329/jbau.v6i2.4821 J. Bangladesh Agril. Univ. 6(2): 271-276, 2008